2020
DOI: 10.12973/eu-jer.9.4.1749
|View full text |Cite
|
Sign up to set email alerts
|

Development of Web-based Application for Teacher Candidate Competence Instruments: Preparing Professional Teachers in the IR 4.0 Era

Abstract: This research aimed to develop a web-based application for teacher candidate competence instruments to prepare professional teachers in the Industrial Revolution 4.0 (IR 4.0) era. Teacher candidate competencies consist of pedagogical, professional, social, and personality competences. This is a research and development with 8 stages, involving the development of instrument grids/ construct, focus group discussions, instrument item development, instrument validation, manual instrument testing, application devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
6
0
6
Order By: Relevance
“…(34) and Goodness of fit Index (GFI) 0.97>0.90 (Kartowagiran et al, 2020;Schermelleh-Engel et al, 2003). In general, the requirements for Goodness of Fit have been fulfilled because the value obtained is within the required interval, so it is said that the model obtained is fit, thus it is concluded that the model used is fit, which means that the instrument construct is good and can be used in terms of model deployment this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…(34) and Goodness of fit Index (GFI) 0.97>0.90 (Kartowagiran et al, 2020;Schermelleh-Engel et al, 2003). In general, the requirements for Goodness of Fit have been fulfilled because the value obtained is within the required interval, so it is said that the model obtained is fit, thus it is concluded that the model used is fit, which means that the instrument construct is good and can be used in terms of model deployment this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Indonesia, teacher certification has no effect on performance or motivation 10 years after certification, implying that certification allowances have little impact on performance. As a result, the graduate evaluation and selection procedure for teacher certification must be modified in order for the govt certification program to meet its goals [51]. They are strongly supported by the leadership of the professional principal, teacher efficacy, courses, discussions, and development through the professional community [58].…”
Section: Elementary School Teacher Professional Competencementioning
confidence: 99%
“…Proses pencarian uang tersebut dilakukan oleh guru dengan cara menyulut korek api pada telapak tangan siswa satu persatu, dengan harapan agar siswanya ada yang mengaku telah mengambil uang tersebut. Kejadian ini sangat disayangkan terjadi dan dilakukan oleh seorang guru yang harusnya memiliki sifat arif dan bijaksana (Kartowagiran et al, 2020).…”
Section: Pendahuluanunclassified
“…Dasar the Law of Comparative Judgment ini lah yang mendorong untuk melakukan penelitian tentang kompetensi kepribadian guru menggunakan metode penskalaan Thurstone. Penelitian sebelumnya mengenai kompetensi kepribadian guru pernah dilakukan oleh Kartowagiran et al (2020) yang menyimpulkan bahwa instrumen kompetensi kepribadian sudah layak digunakan karena sudah memenuhi aspek validitas dan reliabilitas yang baik. Analisis validitas menggunakan Formula Aiken untuk validitas isi, dilanjutkan dengan analisis melalui Exploratory Factor Analysis (EFA) dan Confirmatory Faktor Analisis (CFA) untuk validitas konstruk.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation